The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00701-012-1594-8
|View full text |Cite
|
Sign up to set email alerts
|

Results of endovascular treatment of middle cerebral artery aneurysms after first giving consideration to clipping

Abstract: At our hospital, MCA aneurysms are being treated with endovascular techniques, but in a minority of patients. Despite the rate of residual neck remnants, few retreatments were necessary and few rehemorrhages occurred. The periprocedural complication rate was not insignificant; therefore, in more recent years and at present, most MCA aneurysms are considered for clipping first at our center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…30 , an emerging endosaccular device and reported complete occlusion in 26.7% and a neck remnant in 56.7% of aneurysms at a median of 6-month followup. Use of these novel endoluminal and endosaccular devices requires dual-antiplatelet therapy to prevent thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…30 , an emerging endosaccular device and reported complete occlusion in 26.7% and a neck remnant in 56.7% of aneurysms at a median of 6-month followup. Use of these novel endoluminal and endosaccular devices requires dual-antiplatelet therapy to prevent thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors feel that surgical clipping offers select patients with ruptured MCA aneurysms the best long-term clinical outcome [32, 4043]. …”
Section: Discussionmentioning
confidence: 99%
“…The Kuopio Cerebral Aneurysm Database found [36] that 29% of ruptured MBIF aneurysms presented with preoperative hydrocephalus. Abla et al [32] found that 24.2% of patients presented with hydrocephalus. Obstructive hydrocephalus in the setting of aSAH obviates the need for an external ventricular drain (EVD) which increases the risk of dual antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations